Ineffectiveness in Teacher Bargaining: The Anatomy of a First Strike - Harris, Philipp; Rausch, Peter; Ryan, Samuel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
The objective of this paper is to identify characteristics which distinguish first strike situations from other strike actions. It is based on both collective bargaining and conflict resolution literature as well as the detailed analysis of a recent walkout by a public school teachers' union.